Granulosa Cells: Central Regulators of Female Fertility - Luis Fernando Schütz; Isadora M. Batalha (Endocrines)
Background: Granulosa cells are somatic cells within the ovarian follicle. As the primary site of estradiol production, they are critical regulators of several aspects of female reproduction. This review aims to provide an overview of the physiology of mammalian granulosa cells and their importance for female fertility. Methods: the literature about the function and regulation of granulosa cells was reviewed. Results: a comprehensive summary and discussion of the role of granulosa cells on ovarian steroidogenesis and folliculogenesis, as well as factors that control granulosa cells function, are presented. Conclusion: The functions of granulosa cells are regulated by a plethora of intra- and extra-ovarian factors via autocrine, paracrine, and endocrine pathways, which creates a complex regulatory network. A comprehensive understanding of granulosa cells’ physiology is vital for the development of innovative strategies to enhance reproductive outcomes in several species.